AB1067 Quantity and Quality of Feedback on Clerking Obtained by 4th Year Manchester Medical Students during Rheumatology and Orthopaedics. (15th July 2016) - Lazarewicz, K.; Oldbury, J.; Watson, P.
Abstract : Background: Feedback is the cornerstone of effective clinical teaching [1] allowing students to improve by reinforcing good practice and improving poor practice. The ability to take a clinical history is a key skill required to practise effectively as a doctor. The four week Rheumatology and Orthopaedic placement for the University of Manchester medical students requires them to take a minimum of 12 case histories, at least four of which must be presented to clinicians to obtain feedback. Objectives: To review quantity and quality of feedback on clerking obtained by 4th year Manchester Medical students as a part of Rheumatology and Orthopaedic placement. Methods: A questionnaire survey of 4th year medical students studying Rheumatology and Orthopaedics at the University Hospital of South Manchester was performed to review clinical history taking and feedback during this module. It consisted of 13 questions designed around the four levels of training evaluation described by Kirkpatrick's evaluation framework [2]. It was given to three cohorts of students on the day that they completed their Rheumatology and Orthopaedics block. Results: 43/64 (67.2%) of students responded to the questionnaire, of which 21 students (48.8%) either agreed or strongly agreed that it was easy to find patients from whom to take clinical histories during the placement. However, 18.6% of students reported not achieving the minimum of 12 case histories required. 32.6% of students agreed that it was easy to identify staff from which feedback could be sought, and 44.2% received feedback for at least four clinical histories. The majority of the students (81.4%) agreed that feedback was useful. The content of the feedback that was evaluated in the first two cohorts of students varied greatly, with very few students received feedback covering positive and negative comments as well as ways to improve (Orthopaedics 19.2%; Rheumatology 31.7%). Feedback varied in length of time with 58.1%taking less than five minutes, 25.6% lasting 5–10 minutes and 11.6% lasting 11–15 minutes. Conclusions: Our survey demonstrates that there are some issues with the current system for facilitating student history taking, and obtaining feedback on this. The vast majority of feedback received is perceived as useful. Over half of students are not achieving the amount of feedback that they should receive, hence students are potentially missing out on an important opportunity to improve their clinical performance. Considering the results of this survey the authors plan to develop an intervention to try to increase the quality and quantity of feedback given, similar to the feedback postcard project being piloted in Edinburgh [3], which seems on track to improve both the quality and quantity of feedback during clinical placements. References: Cantillon and Sergent Giving Feedback in clinical settings BMJ 2008;337:a1961 Employing Kirkpatrick's Evaluation Framework to Determine the Effectiveness of Health Information Management Courses and Programs. Rouse D. Perspect Health Inf Manag. 2011(spring);8:1c Feedback Postcards Project. 2016. Feedback Postcards Project. [ONLINE] Available at: https://www.eemec.med.ed.ac.uk/pages/feedback-cards. [Accessed 27 January 2016] Disclosure of Interest: None declared